The Influence of Liquidity and Corporate Social Responsibility Disclosure on Profitability - Carolin Putri Klana; Patria Prasetio Adi (Indonesian Journal of Business Analytics, 2025)
This study examines the influence of liquidity and corporate social responsibility (CSR) disclosure on the profitability of agricultural enterprises listed on the Indonesia Stock Exchange, focusing on the 2021–2023 timeframe. This study was motivated by a significant decline in agriculture sector profitability and inconsistent previous findings. Quantitative associative descriptive approach was used in this research. Purposive sampling resulted in a sample of 18 agricultural companies. SPSS version 27 was utilized as the analytical tool for this analysis. The result shows that, partially, liquidity significantly and positively affects profitability, whereas CSR disclosure does not. However, simultaneously, liquidity and CSR disclosure affect profitability. These findings emphasize the importance of financial stability and CSR for the sustainable growth of the agricultural sector.